2000
DOI: 10.1103/physrevlett.84.3859
|View full text |Cite|
|
Sign up to set email alerts
|

Local Measurement of Nonclassical Ion Heating during Magnetic Reconnection

Abstract: Local ion temperature is measured directly in the well-characterized reconnection layer of a laboratory plasma. These measurements demonstrate definitively that ions are heated due to reconnection and that more than half of the reconnected field energy is converted to ion kinetic energy. Neither classical Ohmic dissipation nor thermalization of energetic flows is sufficent to account for the energy converted, suggesting the importance of non-classical dissipation mechanisms such as wave-particle interactions.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 20 publications
0
30
1
Order By: Relevance
“…A sketch of the best-fit ion velocity distribution function is also displayed (upper right inset). f (v) Note that the distribution is clearly superthermal (E k drift eV) and super-Alfvénic ( eV) with E ഡ 20 E 1 E ഡ 50 thermal drift Alf eV, in contrast to earlier work (Gekelman et al 1982; E 1 200 max Hsu et al 2000). Recall that the peak reconnection EMF is roughly for us, consistent with this result.…”
Section: /2 V P B/ (4pr)contrasting
confidence: 56%
See 1 more Smart Citation
“…A sketch of the best-fit ion velocity distribution function is also displayed (upper right inset). f (v) Note that the distribution is clearly superthermal (E k drift eV) and super-Alfvénic ( eV) with E ഡ 20 E 1 E ഡ 50 thermal drift Alf eV, in contrast to earlier work (Gekelman et al 1982; E 1 200 max Hsu et al 2000). Recall that the peak reconnection EMF is roughly for us, consistent with this result.…”
Section: /2 V P B/ (4pr)contrasting
confidence: 56%
“…This experimental measurement corresponds directly with reconnection-driven bidirectional outflows observed on the Sun (Innes et al 1997) and in the magnetosphere (Phan et al 2000). Recently, Hsu et al (2000) also measured downstream outflow in the axisymmetric device MRX ( ) and found plasma rotation outside the…”
Section: /2 V P B/ (4pr)mentioning
confidence: 99%
“…If the measured ratio E/j is defined as an effective resistivity, η * = E/j, reconnection data from MRX is found to agree with a generalized Sweet-Parker theory based on this effective resistivity (and also including compressibility and downstream pressure) [50]. The second observation is that of direct, nonclassical ion heating during reconnection in MRX current sheets [51]. One possible explanation for these two observations is the presence of turbulence in low-collisionality MRX current sheets, which creates a turbulent anomalous resistivity η * > η sp (so that E θ /η * j θ = 1) and directly heats the ions.…”
Section: Experimental Apparatusmentioning
confidence: 72%
“…Distinctive features include concentration of electric current density, characteristic plasma flows, and ion heating; these are expected theoretically [Priest and Forbes, 2000;Sonnerup, 1979], simulated [e.g., Shay et al, 1998] and observed in the laboratory [e.g., Hsu et al, 2000]. Many of these features are also observed through model dependent interpretations of spacecraft data [e.g., Phan et al, 2000].…”
Section: Introductionmentioning
confidence: 95%